Towards a Logic-based Framework for Representing and Reasoning about Geographic Phenomena - Campelo, Claudio (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2014: Anais do V Workshop de Computação Aplicada a Gestão do Meio Ambiente e Recursos Naturais, 2014)
This paper presents a logic-based approach to representing and reasoning about geographic phenomena. This approach is divided into two major parts. The former consists of a logical model of the Earth surface, which considers its spatial, temporal and thematic dimensions. This model provides improved integration of heterogeneous spatio-temporal data and enables the derivation of implicit data by means of logical inferences. The latter is a logical framework for representing and reasoning about geographic phenomena. This framework is based on the concepts of events and processes and on the relationships that may hold between them. The paper also presents a system prototype implemented to evaluate the applicability of the proposed theory. A case study about deforestation in Brazilian Amazon rainforest was conducted using this prototype, where events and processes are described in terms of changing spatial extensions of geographic features.